2018
DOI: 10.1016/j.ejvs.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Stenting and Endarterectomy for Asymptomatic Carotid Artery Stenosis: A Meta-Analysis of Randomised Controlled Trials

Abstract: Among patients with asymptomatic carotid stenosis, stenting has a significantly higher rate of any peri-procedural stroke and peri-procedural minor stroke than CEA, and similar risk of peri-procedural major stroke, peri-procedural ipsilateral stroke, or MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 34 publications
(45 reference statements)
0
15
0
3
Order By: Relevance
“…Eine weitere Metaanalyse zeigte einen signifikant geringeren Anteil periprozeduraler Schlaganfälle (vor allem leichter Schlaganfall) in der TEA-Gruppe verglichen zu CAS (OR 0,53; 95 %-KI 0,29-0,96). Keine signifikanten Unterschiede gab es in den Endpunkten periprozeduraler Tod, schwerer Schlaganfall, ipsilateraler Schlaganfall und Myokardinfarkt [27]. Nicht zuletzt in der SPACE-2-Studie konnte gezeigt werden, dass der größte Anteil an Schlaganfällen in der interventionellen Behandlung der ACS in der periprozeduralen Phase auftritt [20].…”
Section: Vergleich Thrombendarteriektomie Vs Karotisarterienstentingunclassified
“…Eine weitere Metaanalyse zeigte einen signifikant geringeren Anteil periprozeduraler Schlaganfälle (vor allem leichter Schlaganfall) in der TEA-Gruppe verglichen zu CAS (OR 0,53; 95 %-KI 0,29-0,96). Keine signifikanten Unterschiede gab es in den Endpunkten periprozeduraler Tod, schwerer Schlaganfall, ipsilateraler Schlaganfall und Myokardinfarkt [27]. Nicht zuletzt in der SPACE-2-Studie konnte gezeigt werden, dass der größte Anteil an Schlaganfällen in der interventionellen Behandlung der ACS in der periprozeduralen Phase auftritt [20].…”
Section: Vergleich Thrombendarteriektomie Vs Karotisarterienstentingunclassified
“…With regard to peri-procedural outcomes, a recent meta-analysis of 3901 asymptomatic patients randomly assigned to CEA ( n = 1585) or CAS ( n = 2316) reported that CAS was associated with a significantly higher risk of peri-procedural stroke than CEA (2.6% versus 1.3% respectively; p = 0.04) [ 65 ••]. This was largely driven by more minor strokes following CAS than CEA (2.2% versus 1.0%; p = 0.05) [ 65 ••]. Rates of death, major stroke, ipsilateral stroke and MI were comparable between CEA and CAS [ 65 ••].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This was largely driven by more minor strokes following CAS than CEA (2.2% versus 1.0%; p = 0.05) [ 65 ••]. Rates of death, major stroke, ipsilateral stroke and MI were comparable between CEA and CAS [ 65 ••].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Several randomized controlled trials have demonstrated the safety and efficacy of transfemoral carotid artery stenting (TF-CAS) and carotid endarterectomy (CEA) for symptomatic or asymptomatic CS (6)(7)(8)(9). However, TF-CAS has commonly been considered as an alternative to CEA, which is seen as the gold standard for treating CS (10)(11)(12). Even though TF-CAS has reached equivalent effects on late outcomes as CEA (13) and has been more favorable for patients with higher risks at anatomy or clinical picture (14).…”
Section: Introductionmentioning
confidence: 99%